Karakteristik Penderita Glaukoma Di Rumah Sakit Mata Makassar Periode Tahun 2022 - Arman, Andi Darlina; Irzal, Irzal W; Angky, Meiliaty Ariesta (Fakultas Kedokteran Universitas Bosowa, 2025)
Glaucoma is a neurogenerative disorder in which retinal ganglion cells are degenerating, and causes significant visual disability. The purpose of this study was to determine the characteristics of glaucoma patients who seek treatment at the Rumah Sakit Mata Makassar. The type of research method used is total sampling. The population in this study amounted to 200 patients with a sample size of 170 patients. The sampling method in this study used total sampling. This study uses secondary data obtained from medical records for the period 2022 at the Rumah Sakit Mata Makassar. Based on the results of the study, 56-65 years old with glaucoma as many as 43 people (22%) and ages 5-11 years old with glaucoma as many as 3 people (2%). Gender is not much different, namely 98 women (49%) and 72 men (36%). Patients with a history of hypertension are at risk of glaucoma as many as 67 people (33,5%) and normal as many as 9 people (4.5%). Patients with diabetes mellitus were at risk of glaucoma as many as 150 people (75%) and there was no history of diabetes mellitus as many as 7 people (3.5%). Based on the type of glaucoma, 145 people (72.5%) suffered from POAG and the least was congenital glaucoma, namely 1 (0.5%).